SIFAT MEKANIK KOMPOSIT BERBASIS POLI ASAM LAKTAT (PLA) DAN SERAT SELULOSA TANDAN KOSONG KELAPA SAWIT - Marwanto, . (JURNAL HUTAN LESTARI, 2017)
Poly lactic acid (PLA) is thermoplastic plastic that have potential to replace conventional plastic because it have advantages such as biodegradable and sustainable. ButÂ  PLA have weakness like fragile. The aim of this study is evaluate mechanical properties of composites PLA with additon oil palm empty fruit bunches (EFB) cellulose fibers. The composition of EFB cellulose fibers were 0, 5, 10, 15 and 20 Per Hundred Resin (PHR). Testing sample test sample using Shimadzu Universal Testing Machine with load speed 1 mm / minute and 70 mm gauge length, based on ASTM D-638-02a standard. The sample length is 110 mm, width 6 mm and thick 0,7 mm. All displayed average of 3 repetitions. The results showed that tensile strength and elongation composites neat PLA highest than composite PLA with EFB cellulose fibers showing value respectively 40,20 MPa and 4,25%. The highest value for young modulus in composite PLA with cellulose fiber was noted at 15 PHR EFB cellulose fibers with value of 3,96 GPa. Keywords: Biodegradable, Cellulose Fibers, Mechanical Properties, Oil Palm Empty Fruit Bunches, Polylactic Acid